Factors Causing Non-Performing Loans in the Financial Sector Listed on the Indonesia Stock Exchange in 2017-2022 - Yusuf Faisal; Christine Natania Zefanya; Muhammad Rizky Febrianto (Al-Muhasabah: Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to obtain empirical evidence on the effect of inflation, capital adequacy ratio, loan-to-deposit ratio, operating expenses, and operating income on non-performing loans. This study uses quantitative research. This research was conducted by observing financial sector companies listed on the Indonesia Stock Exchange, totaling 47 companies. The data source used is the company's annual report from 2017-2022. To obtain the results of this study, researchers used Eviews12. The results of this study found that inflation has a negative and statistically insignificant effect on non-performing loans, while the capital adequacy ratio has a positive and statistically insignificant effect on non-performing loans, while the loan to deposit ratio has a positive and statistically insignificant effect on non-performing loans. Furthermore, operating expenses and operating income weaken the effect of inflation on non-performing loans. loan to deposit ratio also strengthens the effect of capital adequacy ratio on non-performing loans. operating expenses and operating income also strengthen the effect of capital adequacy ratio on non-performing loans. This study discusses non-performing loans and the factors that influence them in financial sector companies